2006
DOI: 10.1194/jlr.m600163-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ABCA1 expression in human keratinocytes and murine epidermis

Abstract: Keratinocytes require abundant cholesterol for cutaneous permeability barrier function; hence, the regulation of cholesterol homeostasis is of great importance. ABCA1 is a membrane transporter responsible for cholesterol efflux and plays a pivotal role in regulating cellular cholesterol levels. We demonstrate that ABCA1 is expressed in cultured human keratinocytes (CHKs) and murine epidermis. Liver X receptor (LXR) activation markedly stimulates ABCA1 mRNA and protein levels in CHKs and mouse epidermis. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 50 publications
(58 reference statements)
2
61
0
2
Order By: Relevance
“…This decrease in ABCA1 may reflect a reduction in free cellular cholesterol and a decrease in the conversion of cholesterol to oxysterols, activators of liver X receptor (LXR). Similar to other cells, ABCA1 expression is stimulated by LXR activators in keratinocytes, and an increase in cellular cholesterol activates LXR but a decrease in cellular cholesterol decreases the activation of LXR (155).…”
Section: Jlr: Are the Apolipoproteins That Interact With Lipoprotein mentioning
confidence: 84%
See 1 more Smart Citation
“…This decrease in ABCA1 may reflect a reduction in free cellular cholesterol and a decrease in the conversion of cholesterol to oxysterols, activators of liver X receptor (LXR). Similar to other cells, ABCA1 expression is stimulated by LXR activators in keratinocytes, and an increase in cellular cholesterol activates LXR but a decrease in cellular cholesterol decreases the activation of LXR (155).…”
Section: Jlr: Are the Apolipoproteins That Interact With Lipoprotein mentioning
confidence: 84%
“…LCAT mediates the conversion of cholesterol to cholesteryl esters in lipoprotein particles, which allows for the efficient removal of cholesterol from cells. In addition, recent studies by our laboratory have shown that ABCA1 is made in both the upper and lower epidermis, and acute disruption of the permeability barrier results in the downregulation of ABCA1 expression in both the upper and lower epidermis (155). This decrease in ABCA1 may reflect a reduction in free cellular cholesterol and a decrease in the conversion of cholesterol to oxysterols, activators of liver X receptor (LXR).…”
Section: Jlr: Are the Apolipoproteins That Interact With Lipoprotein mentioning
confidence: 99%
“…ABCA1 is expressed in human keratinocytes and murine epidermis, and LXR activation markedly increases ABCA1 mRNA and protein levels in keratinocytes and mouse epidermis (87). In addition, activators of PPARa and PPARb/y, but not PPARg, also increase ABCA1 expression in human keratinocytes (87).…”
Section: Abca1mentioning
confidence: 99%
“…The effl ux of cholesterol from cells is mediated by ABCA1 (16)(17)(18). Previously, we reported that ABCA1 is expressed in cultured human keratinocytes (CHKs) and murine epidermis, and that liver X receptor (LXR) activation markedly stimulates ABCA1 mRNA and protein levels in CHKs and mouse epidermis ( 19 ). Similar to LXR, activation of other nuclear receptors, including peroxisome proliferatoractivated receptor-␣ (PPAR-␣ ), PPAR-␤ / ␦ , and RXR, also increase ABCA1 expression in CHKs ( 19 ).…”
Section: Microscopy and Immunohistochemistrymentioning
confidence: 99%
“…Previously, we reported that ABCA1 is expressed in cultured human keratinocytes (CHKs) and murine epidermis, and that liver X receptor (LXR) activation markedly stimulates ABCA1 mRNA and protein levels in CHKs and mouse epidermis ( 19 ). Similar to LXR, activation of other nuclear receptors, including peroxisome proliferatoractivated receptor-␣ (PPAR-␣ ), PPAR-␤ / ␦ , and RXR, also increase ABCA1 expression in CHKs ( 19 ). Additionally, increases in cholesterol levels in keratinocytes induced by LDL or mevalonate stimulate ABCA1 expression, while inhibiting cholesterol synthesis with statins, or CS decreases ABCA1 expression in CHKs ( 19 ).…”
Section: Microscopy and Immunohistochemistrymentioning
confidence: 99%